PRODUKTIVITAS DAN BIAYA ALAT BERAT HYDRAULIC STATIC PILE DRIVER PADA PEKERJAAN FONDASI TIANG PANCANG - Reza, Muhammad Reza Syahputra; Farida, Ida (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
The pile foundation is a deep foundation, and can only be done with the help of heavy equipment Hydraulic Static Pile Driver or Diesel Hammer. The research location is in the Banten Islamic Center Building construction project. The selection of piling tools for the project is using Hydraulic Static Pile Driver, because the construction site is close to residential areas so that the right tools are needed for the piling process effectively and according to applicable standards. Therefore, this study aims to determine the productivity value and cost value incurred by the tool. The method used is using the Pile Driver - Hammer equation and the work unit price equation in the PUPR Ministerial Regulation No.28 of 2016. The piling work reviewed was 326 points with depths ranging from 7.5 meters to 35 meters and with a time of 25 minutes to 125 minutes. Based on variations in the use of length and dimensions of poles, the average productivity of piling is 13.98 m / hour. The results of the cost calculation based on the unit price of work for the